Analysis of the cesarean section as cost source - Danilo Nápoles Méndez; Dayana Couto Núñez (Medisan, 2017)
A descriptive and cross-sectional study was carried out during 2014, aimed at exposing the direct and indirect costs related to the cesarean section.  In the analysis the elements for a cost card were integrated such as:  materials, manpower and other expenses; also, the breakdown of each of its components was made and it was obtained that the cost of a cesarean section without complications and with a duration of 30 minutes was $545.62. For the cesarean sections with these characteristics an approximate extrapolation of the expenses in the country for the same year was carried out. It was concluded that is necessary the strict control of this operation since the elevation of its indicator increases the costs that could be used in other necessities in the health system.